Novel agents for pancreatic ductal adenocarcinoma: emerging therapeutics and future directions - Yiyin Zhang; Chao Yang; He Cheng; Zhiyao Fan; Qiuyi Huang; Yu Lu; Kun Fan; Guopei Luo; Kaizhou Jin; Zhengshi Wang; Chen Liu; Xianjun Yu (Journal of Hematology & Oncology, 2018)
Abstract A poor prognosis of pancreatic ductal adenocarcinoma (PDAC) associated with chemoresistance has not changed for the past three decades. A multidisciplinary diagnosis followed by surgery and chemo(radiation)therapy is the main treatment approach. However, gemcitabine- and 5-fluorouracil-based therapies did not present satisfying outcomes. Novel regimens targeting pancreatic cancer cells, the tumor microenvironment, and immunosuppression are emerging. Biomarkers concerning the treatment outcome and patient selection are being discovered in preclinical or clinical studies. Combination therapies of classic chemotherapeutic drugs and novel agents or novel therapeutic combinations might bring hope to the dismal prognosis for PDAC patients.